Spatiotemporal variations and extreme value analysis of significant wave height in the South China Sea based on 71-year long ERA5 wave reanalysis. (August 2021) - Wang, Jichao; Liu, Jincan; Wang, Yue; Liao, Zhihong; Sun, Peidong
Abstract: A thorough understanding of the long-term trends and extreme characteristics in the significant wave height (SWH) contributes greatly to coastal and offshore engineering activities and mitigation of marine disasters. In this study, the annual spatiotemporal variability of the SWH in the South China Sea (SCS) and the return periods for six locations are evaluated based on ERA5 wave reanalysis in a long time period (1950–2020). Long-term trends are estimated by using a popular non-parametric method, the Theil-Sen estimator, and then mapped to show the spatial variability of mean and extreme SWH. Basin-averaged analysis is also performed to investigate the general tendency of the mean SWH in the SCS, with an increasing rate of 0.11 cm/year. The well-known Mann-Kendall test is used to assess the significance of the trends. Significant positive trends in extreme SWH are mainly distributed in the eastern part of the central SCS around the Luzon Strait and the southwestern part of the SCS. In the extreme value analysis, by comparing 2 classical extreme value distribution models combined with 5 sampling methods, the Generalized Pareto Distribution incorporating the Peak Over Threshold (GPD-POT) method has turned out to be suitable for evaluating the return periods in the SCS based on 71-year SWH dataset. Extreme value analysis for different time lengths shows a correlation between the return level and the time span. Small and medium samples may lead to unstable parameter estimation and increased errors. The 100-year return values obtained by GPD-POT using the 71-year wave reanalysis are more credible at P1-P6 with 8.86, 11.79, 11.35, 10.52, 6.50 and 7.71 m, respectively. Both the estimated return periods and the number of extreme events quantified by the Method of Independent Storms (MIS) indicate that extreme events are closely related to the number of tropical cyclones. Seasonally, most extreme events in the SCS occur from June to December, with the summertime maximum SWH situated above the 15th degree of northern latitude and rapidly shifting to south in the fall.